Comparative assessment of small airway dysfunction by impulse oscillometry and spirometry in chronic obstructive pulmonary disease and asthma with and without fixed airflow obstruction - Liwsrisakun, Chalerm; Chaiwong, Warawut; Pothirat, Chaicharn (Frontiers in Medicine, 2023)
Background: Small airways play a major role in the pathogenesis and prognosis of chronic obstructive pulmonary disease (COPD) and asthma. More data on small airway dysfunction (SAD) using spirometry and impulse oscillometry (IOS) in these populations are required. The objective of this study was to compare the two methods, spirometry, and IOS, for SAD detection and its prevalence defined by spirometry and IOS in subjects with COPD, asthma with and without fixed airflow obstruction (FAO). Design: A cross-sectional study. Methods: Spirometric and IOS parameters were compared across four groups (COPD, asthma with FAO, asthma without FAO, and healthy subjects). SAD defined by spirometry and IOS criteria was compared. Results: Two hundred and sixty-two subjects (67 COPD, 55 asthma with FAO, 101 asthma without FAO, and 39 healthy controls) were included. The prevalence of SAD defined by using IOS and spirometry criteria was significantly higher in patients with COPD (62.7% and 95.5%), asthma with FAO (63.6% and 98.2%), and asthma without FAO (38.6% and 19.8%) in comparison with healthy control (7.7% and 2.6%). IOS is more sensitive than spirometry in the detection of SAD in asthma without FAO (38.6% vs.19.8%, p = 0.003) However, in subjects with FAO (COPD and asthma with FAO), spirometry is more sensitive than IOS to detect SAD (95.5% vs. 62.7%, p < 0.001 and 98.2% vs. 63.6%, p < 0.001, respectively). Conclusion: SAD was significantly detected in COPD, and asthma with and without FAO. Although IOS shows more sensitivity than spirometry in the detection of SAD in asthma without FAO, spirometry is more sensitive than IOS in patients with FAO including COPD and asthma with FAO.